Wideband Multi-Port Reflectometer as an Alternative in Reflection Coefficient Measurement - Rashidah Che Yob; Norhudah Seman (Universitas Ahmad Dahlan, 2017)
This paper presents the characterization and operation of an alternative device, which is known as multi-port reflectometer to measure the reflection coefficient of any device under test (DUT). Its configuration is formed by two power dividers (D) and four couplers (Q). The characterization is evaluated through the centres of power circles that also known as q-points. Its operation in the reflection coefficient measurement is tested by using three DUTs. The reflectometer’s good performance and wideband operation are proven between the frequency band of 1 and 6 GHz via the practical hardware measurement in the laboratory.